Epidemiological profile of deaths due to ectopic pregnancy in Brazil between 2000 and 2023 (Research, Society and Development, 2025)
Introduction: Ectopic pregnancy (EG) occurs when the blastocyst implants outside the uterus, and can affect several regions. Due to the difficulty of early identification, diagnosis is usually delayed, increasing maternal risk and mortality in the first trimester. Objective: To analyze the epidemiological profile of deaths due to ectopic pregnancy in Brazil between 2000 and 2023. Methodology: An ecological, time-series study with a quantitative approach, based on data from the Mortality Information System (SIM). The 26 states and the Federal District were analyzed, considering maternal deaths registered under the ICD-10 O00. Descriptive statistics were used and there was no need for ethical approval, according to CNS Resolution No. 674/2022 and STROBE guidelines. Results: Notifications varied over the years, with peaks in 2014 and 2022, followed by declines. About 62.9% of deaths occurred "during pregnancy, childbirth or abortion" (570 cases), and 81.91% were in hospitals (743 cases). The predominant age group was 20 to 29 years (41.12% – 373 cases), with a higher incidence among brown women (55.02% – 499 cases). Regarding education, 31.10% had between 8 and 11 years of schooling, and 62.41% were single. Conclusion: Between 2000 and 2023, maternal deaths from EG in Brazil occurred mostly in women of reproductive age, brown, and with incomplete high school or higher education. The deaths occurred at different stages of pregnancy, mainly in a hospital environment, and were mostly investigated with a summary form.